Fluidic integrated 3D bioprinting system to sustain cell viability towards larynx fabrication. Issue 2 (20th October 2022) - Park, Hae Sang; Lee, Ji Seung; Kim, Chang‐Beom; Lee, Kwang‐Ho; Hong, In‐Sun; Jung, Harry; Lee, Hanna; Lee, Young Jin; Ajiteru, Olatunji; Sultan, Md Tipu; Lee, Ok Joo; Kim, Soon Hee; et al.
Abstract: Herein, we report the first study to create a three‐dimensional (3D) bioprinted artificial larynx for whole‐laryngeal replacement. Our 3D bio‐printed larynx was generated using extrusion‐based 3D bioprinter with rabbit's chondrocyte‐laden gelatin methacryloyl (GelMA)/glycidyl‐methacrylated hyaluronic acid (GMHA) hybrid bioink. We used a polycaprolactone (PCL) outer framework incorporated with pores to achieve the structural strength of printed constructs, as well as to provide a suitable microenvironment to support printed cells. Notably, we established a novel fluidics supply (FS) system that simultaneously supplies basal medium together with a 3D bioprinting process, thereby improving cell survival during the printing process. Our results showed that the FS system enhanced post‐printing cell viability, which enabled the generation of a large‐scale cell‐laden artificial laryngeal framework. Additionally, the incorporation of the PCL outer framework with pores and inner hydrogel provides structural stability and sufficient nutrient/oxygen transport. An animal study confirmed that the transplanted 3D bio‐larynx successfully maintained the airway. With further development, our new strategy holds great potential for fabricating human‐scale larynxes with in vivo‐like biological functions for laryngectomy patients.